Encapsulation of L. fermentum with chitosan-alginate enhances its bioactivity against acrylamide toxicity in D.mel - Swetha Senthil Kumar; Sahabudeen Sheik Mohideen (Scientific Reports)
Abstract Acrylamide (ACR), a neurotoxin typically present in thermally processed foods, is a substantial risk to people. The objective of this research is to develop synbiotic capsules with natural substances such as chitosan, alginate, and L. fermentum. Encapsulation is a significant tool in medicine, helping to improve targeted medication delivery and bioavailability. The chitosan/alginate-encapsulated probiotic (CAP) beads increase the bioavailability of probiotics in the gut, allowing for a more effective response to ACR-induced toxicity. The combination of prebiotic and probiotic activity improves stability, viability, and gastrointestinal delivery. We developed CAP beads and assessed their survivability under simulated gastrointestinal conditions, encapsulating efficiency, and release profile. The efficacy of these beads in reducing the harmful effects of ACR was subsequently investigated using a Drosophila melanogaster model. Under co-exposure and pre-treatment settings, in vivo studies revealed restoration of locomotor activities, redox balance, and ovarian mitochondrial membrane potential in flies treated with CAP beads. Furthermore, implying the indirect impact of CAP beads on gut microbiota and xenobiotic metabolism, pre-treatment with CAP more successfully restored the expression of important antioxidant and stress-related genes, including sod, cat, InR, rpr, and p53.